2016
DOI: 10.1038/srep36538
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of a Topologically Protected Surface State in a Sb2Te2Se Single Crystal

Abstract: A topological insulator (TI) is a quantum material in a new class with attractive properties for physical and technological applications. Here we derive the electronic structure of highly crystalline Sb2Te2Se single crystals studied with angle-resolved photoemission spectra. The result of band mapping reveals that the Sb2Te2Se compound behaves as a p-type semiconductor and has an isolated Dirac cone of a topological surface state, which is highly favored for spintronic and thermoelectric devices because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
4
7
0
Order By: Relevance
“…It is reported that the k F extracted from ARPES and SdH oscillation are different because of the sample inhomogeneity 25, 27 . Our ARPES and SdH oscillation show consistent results that support the high homogeneity of our samples 25, 26 . The k F deduces the surface density of state through the relation n s  =  k F 2 /4 π  = 4.95 × 10 12  cm −2 for a circular Fermi surface.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It is reported that the k F extracted from ARPES and SdH oscillation are different because of the sample inhomogeneity 25, 27 . Our ARPES and SdH oscillation show consistent results that support the high homogeneity of our samples 25, 26 . The k F deduces the surface density of state through the relation n s  =  k F 2 /4 π  = 4.95 × 10 12  cm −2 for a circular Fermi surface.…”
Section: Resultssupporting
confidence: 88%
“…The observed SdH oscillation frequency, F  = 205 T, leads to k F  = 7.8 × 10 6  cm −1 , which is consistent with the value of k F  = 7.3 × 10 6  cm −1 extracted from ARPES from the different batches of the same crystal 26 . It is reported that the k F extracted from ARPES and SdH oscillation are different because of the sample inhomogeneity 25, 27 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…[5][6][7] The theoretical calculation reveals that the Dirac point lies within the gap of the bulk state, 42 and our previous work supports the fact that the Fermi level lies below the Dirac point in our Sb 2 -SeTe 2 topological insulator. 26,43 This band structure of the Sb 2 -SeTe 2 topological insulator is similar to the graphene-TMD hybrid structure. The energy of the light at 325 nm is much larger than the band gap of the bulk state; thus, the photons can easily generate electron-hole pairs.…”
Section: Resultssupporting
confidence: 54%
“…The as-grown crystals were cleaved along the basal plane, producing a silvery shining mirror-like surface, and then prepared for the further experiments. The Raman27, EDS and XPS28 spectrum support that the crystal is Sb 2 SeTe 2 .…”
Section: Experimental Methodsmentioning
confidence: 65%